Microfluidics, BioMEMS, and Medical Microsystems XXI 2023
DOI: 10.1117/12.2647885
|View full text |Cite
|
Sign up to set email alerts
|

A method for the rapid fabrication of solid metal microneedles

Abstract: Microneedles are an emerging technology that offer an alternative to traditional hypodermic needles for drug and vaccine delivery. Less than 1 mm in length, microneedles can penetrate the skin with little to no pain making them a suitable option for the 1-in-10 people that may avoid seeking medical care due to needlephobia. However, there are significant challenges with adapting existing microneedle fabrication methods for large scale manufacturing while matching the repeatability, reliability, and cost of cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Additionally, the manipulation of the MNA density limits the insertion due to the "bed of nails" effect, which is avoided by reducing the density of MNAs or by increasing the width of the MNs [14]. In other findings, different MN widths and densities were manipulated, and it was found that higher widths the reliability of insertion increases, due to the physical properties against needle fracture [15]. Ahn designed a customizable single MN that dramatically affects the insertion force; with those single MN tests, they showed that width minimally affects the required insertion force, whilst the tip radius, or the overall microneedle length increases the resistance significantly after 40 µm [16].…”
Section: Microneedlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the manipulation of the MNA density limits the insertion due to the "bed of nails" effect, which is avoided by reducing the density of MNAs or by increasing the width of the MNs [14]. In other findings, different MN widths and densities were manipulated, and it was found that higher widths the reliability of insertion increases, due to the physical properties against needle fracture [15]. Ahn designed a customizable single MN that dramatically affects the insertion force; with those single MN tests, they showed that width minimally affects the required insertion force, whilst the tip radius, or the overall microneedle length increases the resistance significantly after 40 µm [16].…”
Section: Microneedlesmentioning
confidence: 99%
“…Hence, curving the substrate as shown in Figure 1d pushes the air sideways during insertion. To achieve this, MNs were fabricated onto a flexible substrate using a similar bonding technique as for the solid substrates that were published previously [15]. Only the single microchannel configuration is assessed for the flexible substrate.…”
Section: Microchannels and Flexible Substratesmentioning
confidence: 99%